Ecosystem valuation: Some principles and a partial application - Sian Morse-Jones; R. Kerry Turner; Brendan Fisher; Tiziana Luisetti (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2010)
Understanding the economic value of nature and the services it provides to humanity has become increasingly important for local, national and global policy and decision making. However, problems arise in that it is difficult to obtain meaningful values for goods and services that ecosystems provide which have no formal market, or are characteristically intangible. Additional problems occur when economic methods are applied inappropriately and when the importance of ecosystem maintenance for human welfare is underestimated. In this article we provide clarification to practitioners on important considerations in ecosystem services valuation. We first review and adapt definitions of ecosystem services in order to make an operational link to valuation methods. We make a distinction between intermediate and final ecosystem services and also identify non-monetary ways to incorporate regulatory and support services into decision-making. We then discuss the spatially explicit nature of ecosystem service provision and benefits capture, and highlight the issues surrounding the valuing of marginal changes, non-linearities in service benefits, and the significance of non-convexities (threshold effects). Finally, we argue for a sequential decision support system that can lead to a more integrated and rigorous approach to ecosystem valuation and illustrate some of its features in an Afro-montane and a coastal ecosystem context.
Keywords: 330; Ecosystem services; Ecosystem valuation; Economic valuation; Umweltökonomik; Umwelt; Umweltgüter; Umweltschutz; Opportunitätskosten; Entscheidung